Da Escola em Crise: Posição do Problema - Urbano, Pedro (Revista Portuguesa de Pedagogia, 2011)
Critical reflection on the education crisis in the contemporary affluent societies; an historical perspective from the sumerian “é-dubba” (“tablet house”) to the present schools. Introductory notes.